The oceanic circle - Borgese, Elisabeth Mann (United Nations University Press, 1998)
"This book's title is taken from Mohandas Gandhi's comparison of the social order to the ever-widening circles that result when a stone is dropped in the ocean. This human order encompasses the individual, the village, the nation, the region, and the global community. Just such an order is now emerging in the context of ocean governance, generated by the United Nations' 1982 Convention on the Law of the Sea and the subsequent conventions, agreements and programmes following the 1992 Rio Earth Summit. ... Such an order is needed to solve the most urgent problems of over-fishing and stock depletion; pollution from oceanic, atmospheric and land-based sources; climate and sea-level changes; and biodiversity conservation."--Publisher's description.